Implementasi Kebijakan Percepatan Penurunan Stunting Terintegrasi di Kabupaten Padang Lawas - Karida, Yovika Arfatul; Yusran, Rahmadani; Alhadi, Zikri; Permana, Iip (Journal of Civic Education, 2023)
This study aims to analyze the implementation of policies to accelerate the reduction of stunting in Padang Lawas Regency with a qualitative descriptive method. The research was conducted in several agencies and related parties in Padang Lawas Regency. Data collection techniques were obtained through interviews, observation and documentation. The results show that the implementation of accelerated stunting reduction is carried out in the form of mother and child services, providing iron supplement tablets (TTD), social assistance and provision of sanitation and clean water. However, this program has not been successful due to low awareness of the community to participate in mother and child services at posyandu, low awareness of adolescents and pregnant women to take iron tablet suplements, social assistance that is not on target and limited availability of clean water and adequate sanitation infrastructure. This study concludes that to achieve the policy objective of accelerating stunting reduction, support from the local government, local governments and the wider community is needed.